The impact of cathodal tDCS on the GABAergic system in the epileptogenic zone: A multimodal imaging study - Abuhaiba, Sulaiman I.; Duarte, Isabel C.; Castelhano, João; Dionísio, Ana; Sales, Francisco; Edden, Richard; Castelo-Branco, Miguel (Frontiers in Neurology, 2022)
Objectives: We aimed to investigate the antiepileptic effects of cathodal transcranial direct-current stimulation and mechanisms of action based on its effects on the neurotransmitters responsible for the abnormal synchrony patterns seen in pharmacoresistant epilepsy. This is the first study to test for the impact of neurostimulation on epileptiform interictal discharges, and to measure brain metabolites in the epileptogenic zone and control regions simultaneously in patients with pharmacoresistant epilepsy. Methods: This is a hypothesis-driven pilot prospective single-blinded repeated measure design study in patients diagnosed with pharmacoresistant epilepsy of temporal lobe onset. We included seven patients who underwent two sessions of cathodal stimulation (sham followed by real). Real tDCS session was 20 minutes in duration, had current intensity of 1.5 mA delivered via two surface electrodes that had dimensions of 3 by 4 cm. The cathode electrode was placed at FT7 in center whereas the anode at Oz in center. After each session, we performed electroencephalographic recording to count epileptiform interictal discharges over 30 minutes. We also performed magnetic resonance spectroscopy to measure brain metabolite concentrations in the two areas of interest (epileptogenic zone and occipital region), namely GABA, Glx, and glutathione. We focused on a homogenous sample where the epileptogenic zone and antiepileptic medications are shared among patients. Results: Real c-tDCS decreased the number of epileptiform interictal discharges per minute by 61%, p = 0.013 as compared to sham c-tDCS. GABA/Glx ratio in the epileptogenic zone decreased from 1.611 + 0.22 to 1.079 + 0.195, p = 0.011 after real c-tDCS stimulation of the epileptogenic zone as compared to sham c-tDCS. Conclusion: These results provide a window into the anti-epileptic mechanisms of action of tDCS, based on local and remote changes in GABA/Glx ratio and neural oscillatory patterning responsible for the generation of interictal epileptiform discharges.